Quality of Life Analysis of Primary Glaucoma Patients Based on Glaucoma Quality of Life-15 Score at Dr. Moewardi Hospital Surakarta - Changifer, Stephen; Indrakila, Senyum; Widiati, Retno (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: Visual acuity is vital for human's daily life. Glaucoma is a disease that affects visual acuity. In Indonesia, the number of glaucoma cases is quite high and its therapy focuses on eye health indicators. Whereas, Many studies have demonstrated that the quality of life of glaucoma patients diminishes. This research aimed to determine the quality of life of primary glaucoma patients in Dr. Moewardi hospital.Method: This research was conducted using observational analytic method with cross sectional approach. Sampling process uses probability sampling with purposive sampling method. The subjects of this study were primary glaucoma patients in Dr. Moewardi hospital from July to November 2022. The sample size obtained from the formula was 38 people. Data were analyzed with independent t-test and one-way ANOVA. Result: From the data analysis of GQL-15 questionnaire's answer, it was found that there was a decrease in quality of life marked by higher GQL-15 questionnaire score in older patients, longer duration of diagnosis, partially or totally blind and no history of surgery. There was no increase in GQL-15 questionnaire result on patients with higher level of education. GQL-15 score in patients with longer duration of diagnosis (p-value = 0.011) and lower visual acuity (p-value = 0,000) was statistically significant.Conclusion: Older patient groups, patients with longer duration of diagnosis, blind patients (unilateral or bilateral), and those who had not undergone glaucoma surgery has a worse quality of life. Patients’ visual acuity and duration of diagnosis are significantly correlated with their quality of life.